Delineating the Structure-Dynamics-Binding Differences among BA.1, BA.4/5, and BF.7 SARS-CoV-2 Variants through Atomistic Simulations: Correlation with Structural and Epidemiological Features - Joshi A.; Maurya S.; Mahale A.; Rath S.L.; Tripathi T.; Padhi A.K. (My University, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an RNA virus possessing a spike (S) protein that facilitates the entry of the virus into human cells. The emergence of highly transmissible and fit SARS-CoV-2 variants has been driven by the positive selection of mutations within the S-protein. Notable among these variants are alpha, beta, gamma, delta, and omicron (BA.1), with the latter contributing to significant global health challenges and impacting populations worldwide. Recently, a novel subvariant of BA.1, named BF.7, has surfaced, purportedly exhibiting elevated transmissibility and infectivity rates. In order to comprehend and compare the transmissibility and disease progression characteristics of distinct SARS-CoV-2 variants, we performed an extensive comparative analysis utilizing all-atom molecular dynamics (MD) simulations (in triplicate) to investigate the structural, dynamic, and binding features of BA.1, BA.4/5, and BF.7. Our simulation findings, energetic analysis, and assessment of physicochemical properties collectively illuminate the dominance of the BA.1 variant over the others, a trend that is further substantiated by the sustained global prevalence of BA.1 relative to BA.4/5 and BF.7. Additionally, our simulation results align well with the reported cryoelectron microscopy (cryo-EM) structural data and epidemiological characteristics obtained from the Global Initiative on Sharing All Influenza Data (GISAID). This study presents a comprehensive comparative elucidation of the critical structural, dynamic, and binding attributes of these variants, providing insights into the predominance of BA.1 and its propensity to continuously generate numerous novel subvariants. © 2023 The Authors. Published by American Chemical Society.